GAME KOMPUTER JOJO’S FASHION SHOW: WORLD TOUR SEBAGAI SIMULASI PEMBELAJARAN FESYEN - Vidya Kharishma (Universitas Pendidikan Indonesia, 2016)
The development of information technology and computerization has many impacts in various sectors, one of them is games. It can be used as an alternative of learning medium. Jojo’s Fashion Show: World Tour is is a popular computer game based on the simulation of fashion design. It simulates the process of designing and combining fashion from various countries for fashion shows. This research examines the effectiveness of this game as an alternative medium to learn about fashion. The methods used to analyze the game qualitatively in cognitive domain are the comparison methods between the elements and principles theory of fashion design with the elements and principles of gameplay design in the game. Based on research, the game is quite able to broaden the players’ knowledge both in the vocabulary and types of fashion from various countries. From six elements of fashion theory, the game only introduces and discuses about three elements, which are details, materials and colors. On the other hand, it is still unable to fully apply the theory of the five principles of fashion design. Therefore, Jojo's Fashion Show: World Tour is a computer game that is good enough for introducing fashion in cognitive domain on the level of understanding, but has not reached on the level of application.